2014
DOI: 10.1186/1687-9856-2014-2
|View full text |Cite
|
Sign up to set email alerts
|

Poorer glycaemic control is associated with increased skin thickness at injection sites in children with type 1 diabetes

Abstract: We aimed to assess the association between skin thickness and glycaemic control in children with type 1 diabetes. Forty-five children (51% males) aged 10.5 ± 2.1 years were studied. Thickness of skin layers were determined by ultrasonography, with participants having ultrasound scans of three anatomical regions (abdomen, thigh, and buttocks). Poorer glycaemic control (increasing HbA1c values) was associated with greater thickness of the dermis (p = 0.015), with an estimated thickening of 87 μm with every 1% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This results in pain, inflammation, infection risk, thickening of the skin, tissue necrosis, and nerve damage as a result of continuous glucose monitoring. A smart drug delivery system must be developed to overcome the limitations and drawbacks of open-loop delivery [58][59][60]. The number of articles published in the field of insulin drug delivery by oral administration between 2000 and 2023 indicates that this field has received considerable attention.…”
Section: Delivery Of Insulin Via Polymeric Nanostructuresmentioning
confidence: 99%
“…This results in pain, inflammation, infection risk, thickening of the skin, tissue necrosis, and nerve damage as a result of continuous glucose monitoring. A smart drug delivery system must be developed to overcome the limitations and drawbacks of open-loop delivery [58][59][60]. The number of articles published in the field of insulin drug delivery by oral administration between 2000 and 2023 indicates that this field has received considerable attention.…”
Section: Delivery Of Insulin Via Polymeric Nanostructuresmentioning
confidence: 99%
“…assessment of skin thickness: Epidermis plus dermis layers thickness was defined as skin thickness by using an ATL HDI 5000 ultrasound machine (Phillips Healthcare, Best, Netherlands) equipped with a 12-5 MHz linear array transducer [25], [26]. Assessment of Carotid intimamedia thickness (cIMT) was done by using General Electric medical ultrasonographic machine model: Vivid 7 Pro, GE Vingmed ultrasound AS-Nl90, Horton-Norway equipped with 7.5-10 MHz linear-array transducer) [27].…”
Section: Ultrasonographicmentioning
confidence: 99%
“…Repeated injections around the same spot has been strongly associated with skin thickening around the injection sites. Studies have shown a correlation between increased skin thickening and poor glycaemic control, suggesting that the increased thickness around injection sites prevent the correct dose of insulin from being administered [5].…”
Section: Introductionmentioning
confidence: 99%